2003
DOI: 10.1159/000069897
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Seasonal Variation of Stroke Incidence in Patients with Cardioembolic Stroke due to Atrial Fibrillation

Abstract: A seasonal variation with an incidence peak during the colder period of the year, as well as a circadian distribution with a single peak of stroke onset in the morning hours are described in various countries. Cardioembolic stroke seems to be the most frequent stroke subtype among Greek patients. Atrial fibrillation is identified as the most frequent cause of stroke. Analysis of the temporal pattern of symptom onset in a series of over 300 Greek patients with first-ever cardioembolic acute stroke due to atrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 43 publications
(69 reference statements)
4
13
1
2
Order By: Relevance
“…These results are in accordance with previous fi ndings of excess risk of stroke in atrial fi brillation during winter reported from a small study from Athens, Greece [6].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in accordance with previous fi ndings of excess risk of stroke in atrial fi brillation during winter reported from a small study from Athens, Greece [6].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a small study from Athens, Greece, reported that the risk of stroke in patients with atrial fi brillation is highest during the winter [6]. We undertook the present study to further examine the potential of the risk of stroke during winter in patients with atrial fi brillation.…”
mentioning
confidence: 98%
“…Stroke frequency during the nocturnal hours changes in different reports. Most studies, however, agree in finding a lower frequency than expected for this time [8,33]. Some mechanisms have been postulated as an explanation for this pattern, especially the circadian variation in arterial pressure [13,18,30].…”
mentioning
confidence: 87%
“…16 One small series of approximately 300 Greek patients with first-ever cardio embolic acute stroke due to AF also revealed a seasonal peak during winter and a decline of stroke occurrence during summer. 17 Assuming a seasonal variation in hospital admissions with stroke in patients with AF, we would expect to see similar temporal patterns in countries from different parts of the world. However, we are unaware of any data comparing seasonal changes over a comparable time period between two countries, irrespective of seasonality shift by being in the northern or southern hemisphere.…”
Section: Strengths and Limitationsmentioning
confidence: 97%